Competence model as a tool for estimation of state of IT-companies in university’s Business centre - Lytvynov, V.V.; Saveliev, M.V.; Skiter, I.S.; Trunova, O.V. (Математичні машини і системи, 2015)
This paper discusses the business center at the university as a mechanism for the transfer of new technology to industry. There are four types of tools proposed for IT-companies, among which the construction of models of competence. The concept of a competence model Start-Up and Spin-Off companies is formulated. An algorithm of a model of competence forming for Start-Up-companies is developed. It includes: mathematical modeling of the process of learning through cognitive maps, thus optimizing the process of formation of competence; detection algorithm list of the most sought-after competencies based on the method of paired comparisons; assessment of competence at the current time using features such as the level of formation of competences, the level of contribution to the discipline of competence, loss of competence. У статті розглядається бізнес-центр при університеті як механізм передачі нових наукоємних технологій промисловості. Для IT-компаній пропонуються чотири види інструментального вирішення поставлених завдань, серед яких побудова моделі компетенції компанії. Сформульовано концепції створення моделі компетенції Start-Up і Spin-Off компаній. Розроблено комплексний алгоритм формування моделі компетенції Start-Up-компанії, що містить математичне моделювання процесу навчання за допомогою когнітивних карт, що дозволяє оптимізувати процес формування компетенцій; алгоритм виявлення переліку найбільш запитаних компетенцій на основі методу парних порівнянь; оцінку стану компетенції на поточний момент часу, використовуючи такі характеристики, як рівень формування компетенцій, рівень вкладу дисципліни в компетенцію, втрати компетенції. В статье рассматривается бизнес-центр при университете как механизм передачи новых наукоемких технологий промышленности. Для IT-компаний предлагаются четыре вида инструментального решения поставленных задач, среди которых построение моделей компетенции компании. Сформулированы концепции создания модели компетенции Start-Up и Spin-Off компаний. Разработан комплексный алгоритм формирования модели компетенции Start-Up-компании, включающий математическое моделирование процесса обучения с помощью когнитивных карт, позволяющее оптимизировать процесс формирования компетенций; алгоритм выявления перечня наиболее востребованных компетенций на основе метода парных сравнений; оценку состояния компетенции на текущий момент времени, используя такие характеристики, как уровень формирования компетенций, уровень вклада дисциплины в компетенцию, потери компетенции.